An application of developmental genetic programming for automatic creation of supervisors of multi-task real-time object-oriented systems - Sapiecha, Krzysztof; Ciopinski, Leszek; Deniziak, Stanislaw (2014 Federated Conference on Computer Science and Information Systems, 2014)
A concept of artificial supervisor of multi-task real-time object-oriented system is introduced. Next, a procedure for automatic creation of artificial supervisors is presented. The procedure is based on developmental genetic programming. As an input data, UML diagrams are used. A representative example of creation of a supervisor of building a house illustrates the procedure. The efficiency of the procedure from various points of view and comparison considerations are given.